The Truth Within: A History of Inwardness in Christianity, Hinduism, and Buddhism, by Gavin Flood - Charet, F.X. (Religions of South Asia, 2015)
The Truth Within: A History of Inwardness in Christianity, Hinduism, and Buddhism, by Gavin Flood. Oxford: Oxford University Press, 2013. xviii + 310 pp. £65.00. ISBN 978-0-19968-456-4 (hardback).